2014
DOI: 10.3109/02699052.2014.934285
|View full text |Cite
|
Sign up to set email alerts
|

Identifying longitudinal trajectories of emotional distress symptoms 5 years after traumatic brain injury

Abstract: Resilience was the most common trajectory following TBI. Patients characterized by recovery and chronic trajectories required attention and long-term clinical monitoring of their symptoms. Future research would benefit from longitudinal studies to analyse emotional distress symptoms and the strength of resilience over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 61 publications
(93 reference statements)
6
16
1
Order By: Relevance
“…Higher scores are indicative of higher depression and/or anxiety symptoms. The HADS has good internal consistency [Cronbach's α = 0.83 anxiety; α = 0.82 depression; ( 66 )], and has been found to be a reliable and valid measure of emotional distress in TBI populations ( 67 , 68 ).…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores are indicative of higher depression and/or anxiety symptoms. The HADS has good internal consistency [Cronbach's α = 0.83 anxiety; α = 0.82 depression; ( 66 )], and has been found to be a reliable and valid measure of emotional distress in TBI populations ( 67 , 68 ).…”
Section: Methodsmentioning
confidence: 99%
“…The independent variables used in this study were: sex (male vs. female), age at time of injury (in years), relationship status at hospital admission (partnered [married/cohabitant] vs. single), education (0-9 years, 10-12 years, 13-16 years, 17 + years), employment status prior to admission (employed vs. unemployed), occupation prior to admission (blue collar [physical work] vs. white collar [nonphysical work]), acute Glasgow Coma Scale (GCS) score (3)(4)(5)(6)(7)(8)(9)(10)(11)(12), cause of injury (traffic accident vs. other), length of PTA (number of days), computed tomography (CT) head Marshall scores (less severe [no visible injury or small intracranial injury, scores 1-2] and more severe [significant intracranial abnormalities, scores 3-5]) 39 on the ''worst'' CT scan within the first 24 h, and Injury Severity Score (range from 1-75 [best to worst]).…”
Section: Instrumentsmentioning
confidence: 99%
“…4 A large body of literature has documented adverse cognitive, behavioral, emotional, and physical outcomes in individuals with TBI, as well as reduced family and social functioning. [5][6][7][8][9][10][11][12][13] Unfortunately, individuals with TBI often find that these symptoms persist long after injury and ultimately give rise to a host of limitations in activities of daily living. 14 Taken together, the wide range and pervasive nature of TBI sequelae can severely restrict community integration.…”
Section: Introductionmentioning
confidence: 99%
“…1,9 A rich body of literature on long-term outcomes post-TBI has shown that a significant number of TBI survivors carry functional disability long after the initial injury and such disability varies sig-nificantly among individuals. [9][10][11][12][13][14][15][16][17][18] Moreover, studies have suggested that patients with moderate-to-severe TBI could experience a slow or plateaued recovery in the functional measures of the Extended Glasgow Outcome Scale (GOS-E) 18 or the Functional Independence Measures (FIM TM ), 19,20 approximately 1 year or even earlier postinjury. 21,22 These findings point to the chronic effects of TBI that can affect a person's health and social environment long after acute medical treatment and rehabilitation, 23 raising an important question as to whether patients with disability receive the support and rehabilitation they need over time.…”
Section: Introductionmentioning
confidence: 99%